Combining lean teaching and learning with eduScrum. (2017) - Dinis-Carvalho, José; Fernandes, Sandra; Filho, José Carlos Reston
EduScrum and Lean Teaching and Learning (LTL) are two student-centred learning approaches where the greatest responsibility for learning is transferred from the teacher to the student. This paper aims to analyse these two approaches, eduScrum and Lean Teaching and Learning (LTL), and propose a set of LTL features that could be adopted by eduScrum and vice-versa to enhance better teaching and learning in higher education. A deep review of the background, description and step-by-step implementation of each of the approaches is explored in the paper. Based on a critical analysis of best practices from each approach, the authors present a set of guidelines for improvements in each approach based on the best practices of the other approach, discussing specific features, activities or artefacts which can be introduced to significantly improve the other model and lead to greater quality in the teaching and learning process.